Long‐Term Persistence of Donor Alveolar Macrophages in Human Lung Transplant Recipients That Influences Donor‐Specific Immune Responses. Issue 8 (23rd May 2016) - Nayak, D. K.; Zhou, F.; Xu, M.; Huang, J.; Tsuji, M.; Hachem, R.; Mohanakumar, T.
Abstract : Steady‐state alveolar macrophages (AMs) are long‐lived lung‐resident macrophages with sentinel function. Evidence suggests that AM precursors originate during embryogenesis and populate lungs without replenishment by circulating leukocytes. However, their presence and persistence are unclear following human lung transplantation (LTx). Our goal was to examine donor AM longevity and evaluate whether AMs of recipient origin seed the transplanted lungs. Origin of AMs was accessed using donor–recipient HLA mismatches. We demonstrate that 94–100% of AMs present in bronchoalveolar lavage (BAL) were donor derived and, importantly, AMs of recipient origin were not detected. Further, analysis of BAL cells up to 3.5 years post‐LTx revealed that the majority of AMs (>87%) was donor derived. Elicitation of de novo donor‐specific antibody (DSA) is a major post‐LTx complication and a risk factor for development of chronic rejection. The donor AMs responded to anti‐HLA framework antibody (Ab) with secretion of inflammatory cytokines. Further, in an experimental murine model, we demonstrate that adoptive transfer of allogeneic AMs stimulated humoral and cellular immune responses to alloantigen and lung‐associated self‐antigens and led to bronchiolar obstruction. Therefore, donor‐derived AMs play an essential role in the DSA‐induced inflammatory cascade leading to obliterative airway disease of the transplanted lungs. Abstract : Donor alveolar macrophages persist in human lung transplant recipients for up to 3.5 years and may a play a role in the development of donor‐specific immune responses and graft rejection. See also the editorial from Burlingham et al onpage 2247 .